Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Use of cork powder and granules for the adsorption of pollutants: a review. - Pintor, Ariana M A; Ferreira, Catarina I A; Pereira, Joana C; Correia, Patrícia; Silva, Susana P; Vilar, Vítor J P; Botelho, Cidália M S; Boaventura, Rui A R (Water research, 2012)
Cork powder and granules are the major subproducts of the cork industry, one of the leading economic activities in Portugal and other Mediterranean countries. Many applications have been envisaged for this product, from cork stoppers passing through the incorporation in agglomerates and briquettes to the use as an adsorbent in the treatment of gaseous emissions, waters and wastewaters. This paper aims at reviewing the state of the art on the properties of cork and cork powder and their application in adsorption technologies. Cork biomass has been used on its original form as biosorbent for heavy metals and oils, and is also a precursor of activated carbons for the removal of emerging organic pollutants in water and VOCs in the gas phase. Through this literature review, different potential lines of research not yet explored can be more easily identified.
Keywords: activated carbon; Adsorption; Cork granules; cork powder; Heavy metals; Pollutants

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology